Evaluation of PtAu/MWCNT (Multiwalled Carbon Nanotubes) electrocatalyst performance as cathode of a proton exchange membrane fuel cell. (15th August 2016) - Beltrán-Gastélum, M.; Salazar-Gastélum, M.I.; Félix-Navarro, R.M.; Pérez-Sicairos, S.; Reynoso-Soto, E.A.; Lin, S.W.; Flores-Hernández, J.R.; Romero-Castañón, T.; Albarrán-Sánchez, I.L.; Paraguay-Delgado, F.
Abstract: A comparative study between PtAu/MWCNT and Pt/C (commercial) as cathodic electrocatalyst of H2 /O2 fuel cell is performed. PtAu/MWCNT is synthesized using the reverse microemulsion method and this procedure is scaled-up in order to prepare membrane-electrode assemblies for fuel cells with an active area of 9 cm 2 . Those electrocatalysts are characterized by both physicochemical techniques and electrochemical measurements to evaluate their catalytic activity for ORR (Oxygen Reduction Reaction). In the half-cell study, PtAu/MWCNT show higher kinetic current density as cathodic electrocatalyst compared with Pt/C. Likewise, in a fuel cell hardware the maximum power density is significantly higher for PtAu/MWCNT cathode (625 mW cm −2 at 0.426 V) when compared with Pt/C anode (355 mW cm −2 at 0.499 V). Highlights: PtAu/MWCNT was synthesized by reverse microemulsión method. PtAu/MWCNT and Pt/C were characterized by microscopic and spectroscopic techniques. Both materials were studied as catalysts for ORR by electrochemical techniques. Catalysts were used to prepare MEA's, the performance in fuel cell was evaluated. Maximum power densities were 625 mW cm −2 for PtAu/MWCNT and 355 mW cm −2 for Pt/C.